It never rains but it pours: COVID-19 pandemic impact on mental health in older adults: Andrea Amerio. (25th October 2022) - Amerio, A; Stival, C; Lugo, A; Fanucchi, T; Cavalieri d'Oro, L; Iacoviello, L; Odone, A; Zucchi, A; Gallus, S; Serafini, G
Abstract: Italy was the first country to be hit by the 2019 coronavirus disease (COVID-19) in Europe holding one of the highest clinical burdens. Older adults are those paying the highest price for the COVID-19 emergency. Within the Lost in Lombardy project, a web-based cross-sectional study assessing the prevalence of depressive and anxiety symptoms, hopelessness and insomnia before and during the COVID-19 pandemic, was conducted on a representative sample of 4, 400 older adults aged 65 years or more from the Lombardy region recruited between November 17th and 30th 2020. The prevalence of depressive symptoms increased by + 112% during the pandemic, anxiety symptoms by + 136%, insufficient sleep by + 12%, unsatisfactory sleep by + 15%. Feelings of hopelessness were more frequent among women compared to men (15.1% vs. 10.4%) and increased with increasing age. A worsening in each of the four specific mental health outcomes was more frequently observed in women (OR = 1.50, depression; OR = 1.31, anxiety; OR = 1.57, sleep quality; OR = 1.38, sleep quantity), in subjects who decreased their physical activity during the pandemic (OR = 1.64, depression; OR = 1.48, anxiety; OR = 2.05, sleep quality; OR = 1.28, sleep quantity), and with increasing number of pre-existing chronic diseases (p for trend<0.001 for depression and anxiety; p for trend=0.010 for sleep quality; p for trend=0.012 for sleep quantity). A worsening in depressive symptoms was more frequently observed in more educated subjects (p for trend=0.008), while a worsening in anxiety symptoms in subjects living in main towns compared to outskirt with an economic status below the mean. The use of at least one psychotropic drug - mostly antidepressants/anxiolytics - increased by + 26% compared to pre-pandemic. The protection of the mental health status of this vulnerable segment of population needs to be recognized as a real public health priority.